Factors influencing the preimmune antibody repertoire - Kraj, P (Folia biologica, 1997)
Preimmune antibody repertoire is not a statistical representation of all germ-line VH, D, JH and VL, JL segments encoding heavy and light chains, respectively. The antibody repertoire is biased towards a fraction of VH and VL gene segments in fetal/neonatal as well as adult life. The repertoire bias starts at the surface Ig-negative pre-B cells and persists throughout B-cell ontogeny. Antigen-independent processes like preferential rearrangements of VH, D and JH segments and pairing of the heavy and surrogate light chain operate at the surface Ig-negative pre-B cell stage. Subsequently B cells may be subject to self-antigen selection based on the specificity of their surface receptors.
Keywords: B-lymfocyty; Fetus; imunoglobuliny - fragmenty; modely imunologické; zvířata; B-Lymphocytes; novorozenec; Immunoglobulins; Genes, Immunoglobulin; Aging; Animals; tvorba protilátek; Adult; Immunoglobulin Fragments; imunoglobuliny; Antibody Formation; stárnutí; dospělí; plod; Models, Immunological; lidé; geny pro imunoglobuliny; Humans; Infant, Newborn